PENGGUNAAN MEDIA PIXTON UNTUK PENINGKATAN KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS XII SMAN 1 DRIYOREJO - Trirezekhi, Kisy Tirza; Wahyuningsih, Fahmi (LATERNE, 2024)
Writing skills become a mandatory skill for learners in learning German. The German language course at SMAN 1 Driyorejo is one of the compulsory subjects of interest. Based on the information obtained from interviews with the German language teacher of SMAN 1 Driyorejo concluded that the grades of the students of class XII SMAN 1 Driyorejo varied considerably in the skills of writing in German. If we look at the daily grades also, which is the Minimum Continuity Criteria (KKM), some of the students’ grades have been reached and need to be improved in learning. However, there are several factors that cause many learners to have difficulty in writing skills. To overcome this problem, it is necessary to consider a variety of learning and writing materials that are more interactive. Pixton media encourages collaboration between learners. This study applied quantitative research methods with a pre-experimental design one group pretest-posttest. The population in this study was the class XII pupils of SMAN 1 Driyorejo with a total of 35 pupils. Then the result used in this study is the result of the learners’ learning score based on the Pretest average score was 54.5. After the pretest, the next stage is the Treatment test (treatment) and then after the next stage is the Poststest, where the result obtained is the student’s grade with an average grade of 71.17. After performing the above test, we found a record of the learning results before and after using the pixon media on the students of class XII of Driyorejo 1st High School.